Multiparticle correlations and higher order harmonics in pPb collisions at root s(NN)=8.16 TeV - Wang, Quan (2019)
The elliptic and higher-order azimuthal anisotropy Fourier harmonics (v(n)) are obtained for pPb collisions at root s(NN) = 8.16 TeV over a wide range of event multiplicities based on multiparticle correlations. The data were collected by the CMS experiment during the 2016 LHC run. A sample of peripheral PbPb collisions at root s(NN) = 5.02 TeV covering a similar range of event multiplicities to the pPb results is also analyzed for comparison. The ratios of different harmonic moments are obtained for both v(2) and v(3) with high precision, which allows a direct comparison to theoretical predictions assuming a hydrodynamic evolution of the created medium with initial-state density fluctuations, particularly probing the non-Gaussian nature of initial-state fluctuations in small collision systems. The presented results provide crucial insights into the origin of collective long-range correlations observed in small collision systems.